2019
DOI: 10.1038/s41467-019-11526-w
|View full text |Cite
|
Sign up to set email alerts
|

Saturation mutagenesis of twenty disease-associated regulatory elements at single base-pair resolution

Abstract: The majority of common variants associated with common diseases, as well as an unknown proportion of causal mutations for rare diseases, fall in noncoding regions of the genome. Although catalogs of noncoding regulatory elements are steadily improving, we have a limited understanding of the functional effects of mutations within them. Here, we perform saturation mutagenesis in conjunction with massively parallel reporter assays on 20 disease-associated gene promoters and enhancers, generating functional measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
207
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(221 citation statements)
references
References 76 publications
(120 reference statements)
14
207
0
Order By: Relevance
“…These results revealed cis and trans regulators of a previously unrecognized mechanism that activates the endogenous INS gene. Transcriptional regulatory DNA variants play a central role in human disease 44 , yet so far most efforts have investigated their function in experimental systems that do not consider their in vivo impact [45][46][47] . This is a major limitation, because it is currently clear that gene regulation entails a complex interplay between elements that are difficult to reproduce outside of an in vivo context, including chromatin structure, epigenetic chemical modifications, or noncoding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed cis and trans regulators of a previously unrecognized mechanism that activates the endogenous INS gene. Transcriptional regulatory DNA variants play a central role in human disease 44 , yet so far most efforts have investigated their function in experimental systems that do not consider their in vivo impact [45][46][47] . This is a major limitation, because it is currently clear that gene regulation entails a complex interplay between elements that are difficult to reproduce outside of an in vivo context, including chromatin structure, epigenetic chemical modifications, or noncoding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the overall transcriptional levels of developmental genes must be tightly controlled for normal development, as gain-of-function and hypomorph mutants, or RNA-seq experiments show. A number of studies have taken activity levels into account in individual cells in cell culture experiments (e.g., (King et al, 2020;Kircher et al, 2019;Kwasnieski et al, 2012)) or dissociated tissue (e. g., (Farley et al, 2015)), but in this case the information on spatio-temporal variation (the pattern), is lost. By contrast, other studies have quantified pattern elements of enhancer activity but with limited spatial resolution (Crocker et al, 2015;Dufourt et al, 2018)).…”
Section: Introductionmentioning
confidence: 99%
“…We validated this model against melanoma ATAC-seq data from other species, as well as through functional enhancer-reporter assays. We have shown that DeepMEL outperforms other models in a benchmark study using saturation mutagenesis of the IRF4 enhancer, measured by a massively parallel enhancer reporter assay 26 . DeepMEL is able to accurately predict the impact of enhancer mutations in the IRF4 enhancer, and between species.…”
Section: Mainmentioning
confidence: 99%